Anacardic Acid Inhibits Estrogen Receptor α–DNA Binding and Reduces Target Gene Transcription and Breast Cancer Cell Proliferation - David J. Schultz; Nalinie S. Wickramasinghe; Margarita M. Ivanova; Susan M. Isaacs; Susan Dougherty; Yoannis Imbert-Fernandez; Albert R. Cunningham; Chun‐Yuan Chen; Carolyn M. Klinge (2010)
Abstract Anacardic acid (AnAc; 2-hydroxy-6-alkylbenzoic acid) is a dietary and medicinal phytochemical with established anticancer activity in cell and animal models. The mechanisms by which AnAc inhibits cancer cell proliferation remain undefined. AnAc 24:1ω5 was purified from geranium (Pelargonium × hortorum) and shown to inhibit the proliferation of estrogen receptor α (ERα)–positive MCF-7 and endocrine-resistant LCC9 and LY2 breast cancer cells with greater efficacy than ERα-negative primary human breast epithelial cells, MCF-10A normal breast epithelial cells, and MDA-MB-231 basal-like breast cancer cells. AnAc 24:1ω5 inhibited cell cycle progression and induced apoptosis in a cell-specific manner. AnAc 24:1ω5 inhibited estradiol (E2)–induced estrogen response element (ERE) reporter activity and transcription of the endogenous E2 target genes pS2, cyclin D1, and cathepsin D in MCF-7 cells. AnAc 24:1ω5 did not compete with E2 for ERα or ERβ binding, nor did AnAc 24:1ω5 reduce ERα or ERβ steady-state protein levels in MCF-7 cells; rather, AnAc 24:1ω5 inhibited ER-ERE binding in vitro. Virtual screening with the molecular docking software Surflex evaluated AnAc 24:1ω5 interaction with ERα ligand binding (LBD) and DNA binding (DBD) domains in conjunction with experimental validation. Molecular modeling revealed AnAc 24:1ω5 interaction with the ERα DBD but not the LBD. Chromatin immunoprecipitation experiments revealed that AnAc 24:1ω5 inhibited E2-ERα interaction with the endogenous pS2 gene promoter region containing an ERE. These data indicate that AnAc 24:1ω5 inhibits cell proliferation, cell cycle progression, and apoptosis in an ER-dependent manner by reducing ER-DNA interaction and inhibiting ER-mediated transcriptional responses. Mol Cancer Ther; 9(3); 594–605